Diagnostic Injections About the Shoulder. Issue 12 (December 2017) - McFarland, Edward; Bernard, Johnathan; Dein, Eric; Johnson, Alex
Abstract : Injections about the shoulder serve diagnostic as well as therapeutic purposes. Diagnosis of shoulder conditions, such as rotator cuff tears, acromioclavicular joint pathology, subacromial impingement or anterolateral pain syndrome, glenohumeral joint pathology, suprascapular nerve entrapment, and biceps tendon pathologies, is often complicated by concomitant conditions with overlapping symptoms and by inconclusive physical examination and imaging results. Injections of anesthetic agents can often help clinicians locate the source of pain. However, technique and accuracy of needle placement can vary by route. Accuracy is often improved with the use of ultrasonography guidance, although studies differ on the benefits of guided versus unguided injection.